Corynoline Alleviates Osteoarthritis Development via the Nrf2/NF-κB Pathway. (28th July 2022) - Li, Sunlong; Shi, Yifeng; Zhang, Shuhao; Li, Haobin; Ye, Ziyang; Kong, Jiangqian; Hong, Weijun; Tu, Yiting; Ren, Jiaping; Meftah, Zaher; Xie, Chenglong; Wang, Xiangyang; et al.
Abstract : Purpose . OA is a multifactorial joint disease in which inflammation plays a substantial role in the destruction of joints. Corynoline (COR), a component of Corydalis bungeana Turcz., has anti-inflammatory effects. Materials and Methods . We evaluated the significance and potential mechanisms of COR in OA development. The viabilities of chondrocytic cells upon COR exposure were assessed by CCK-8 assays. Western blot, qPCR, and ELISA were used to assess extracellular matrix (ECM) degeneration and inflammation. The NF- κ B pathway was evaluated by western blot and immunofluorescence (IF). Prediction of the interacting proteins of COR was done by molecular docking, while Nrf2 knockdown by siRNAs was performed to ascertain its significance. Micro-CT, H&E, Safranin O-Fast Green (S-O), toluidine blue staining, and immunohistochemical examination were conducted to assess the therapeutic effects of COR on OA in destabilization of medial meniscus (DMM) models. Results . COR inhibited ECM degeneration and proinflammatory factor levels and modulated the NF- κ B pathway in IL-1 β -treated chondrocytes. Mechanistically, COR bound Nrf2 to downregulate the NF- κ B pathway. Moreover, COR ameliorated the OA process in DMM models. Conclusion . We suggest that COR ameliorates OA progress through the Nrf2/NF- κ B axis, indicating COR may have a therapeutic potential for OA.